If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) + -6(2x + -6) = 0 Reorder the terms: 3(-5 + 2x) + -6(2x + -6) = 0 (-5 * 3 + 2x * 3) + -6(2x + -6) = 0 (-15 + 6x) + -6(2x + -6) = 0 Reorder the terms: -15 + 6x + -6(-6 + 2x) = 0 -15 + 6x + (-6 * -6 + 2x * -6) = 0 -15 + 6x + (36 + -12x) = 0 Reorder the terms: -15 + 36 + 6x + -12x = 0 Combine like terms: -15 + 36 = 21 21 + 6x + -12x = 0 Combine like terms: 6x + -12x = -6x 21 + -6x = 0 Solving 21 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -6x = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -6x = 0 + -21 -6x = 0 + -21 Combine like terms: 0 + -21 = -21 -6x = -21 Divide each side by '-6'. x = 3.5 Simplifying x = 3.5
| 1/2×-3=11 | | (3a-1)+(2a+1)+(5a-2)=28 | | 4d-45d=-8 | | 4(-7x+8)=3x+32 | | 36/60=x/100 | | -5x+5=2x-16 | | 3a-1=x | | 77.50=0.15x+10 | | x^2-.2x+0.05=0 | | -1-n=-4(3n+3) | | 5x+12-x=12+4x | | 36/200 | | Y-9=(11/4)x-2 | | 3c-5=2c+50 | | 3-2(2x-3)+3(4x-1)=-20 | | 6x+3=-5x+7 | | 7x-5=8x-14 | | (u+4)(u+4)=2u^2+17u+34 | | 6x+3=-5x+-7 | | 2x-3y-2z=4x+3y | | m/s | | -8x-x+5=14 | | 3x+50=2x+80 | | 8(4n+7)=27+3n | | X+y=27.5 | | 6[-3x+3+5(x+1)]=7x-5 | | 3x+50=2x*80 | | 5.7=3.2d-8 | | 13-7y=6 | | y=0.15x+10 | | 3(y-1)=2x+2 | | 39=-6(4n-3) |